Analisis Pemberdayaan Masyarakat Melalui Program Pendidikan Kesetaraan Paket C pada PKBM Kedondong - Siti Sholikhatur Rohmah; Ridwan Ridwan; Sri Wahyuni (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study examines how PKBM Kedondong's Package C Equality Education Program empowers the community. Through the Package C equality education program at PKBM Kedondong, this study seeks to characterize the stages of awareness, knowledge transformation, and enrichment of community empowerment. This study is qualitative in nature. Package C students, package C teachers, and managers served as the research subjects. Observation, interviewing, and documentation research techniques were used to gather data. Data verification (conclusion), data display, and data reduction are the methods employed in data analysis. According to the research findings, there are three stages in the community empowerment process at PKBM Kedondong through the Package C Equality Education Program. The first stage is awareness, which has been well- socialized, as evidenced by the usage of word-of-mouth to disseminate knowledge. Second, the learning activity process that is part of the knowledge transformation stage consists of: Package C managers and tutors handle the planning stage, which includes creating a syllabus and a Learning Implementation Plan (RPP). During the in-person learning implementation stage, modules, e-books, YouTube, and the internet are used as media, and lectures, Q&A sessions, and discussions are the methods employed. At this point, the evaluation stage seeks to gauge the students' performance in the learning process of package C equivalency education. Thirdly, the effectiveness of the enrichment stage's implementation is demonstrated by the students' learning outcomes and the post-program coaching that is offered.